Simulation of loads on operating device of peat-cutting unit with regard to errors in the cutting elements arrangement - Konstantin V. Fomin (Горные науки и технологии, 2022)
The practice of using units with milling-type operating devices showed their insufficient reliability, which leads to deterioration of the units’ performance. The reasons for this are high dynamic loads in structural members, which are caused by external resistance forces on a milling cutter. They have random, sharply variable nature due to structural heterogeneity of a peat deposit, its random physical and mechanical properties, the presence of wood inclusions in it, as well as periodic interaction of blades with the deposit, and many other factors. In this case, the parameters of actual milling cutter, due to manufacturing and installation errors, differ from those specified in the “ideal” design. In addition, wear and irreversible deformations of cutting elements (blades) occur during operation. As a result the position of blades in a cutter body differs from the “ideal” positioning pattern. The purpose of the paper is to develop a model of section moment on a milling cutter when interacting with a peat deposit in the process of technological operations, taking into account the influence of the error of blade positioning on a cutter body. Expressions for calculating the moment spectral density were obtained. Its characteristic features were analyzed. Errors in positioning of cutting elements on a cutter body lead to changes in the magnitude and nature of the load and its frequency content. In this case, new, additional components appear at frequencies multiple of the cutter’s angular velocity, enriching the load spectrum and increasing its variance. Their magnitude is determined by the cumulative value of the errors. As an example, an analysis of the influence of the error in positioning cutting elements on the spectral density for the operating device of MTP-42 deep milling machine is given. The study results are of practical value and should be taken into account in the calculation of dynamic loads in designing structural members of milling units, especially if their operating devices have a large number of blades, use fine feeds, and when the natural frequencies of the structural members are equal to or multiple of the angular speed of a milling cutter.